In vitro maturation is a viable option for urgent fertility preservation in young women with hematological conditions. Issue 4 (3rd March 2020) - Sonigo, Charlotte; Bajeux, Jeanne; Boubaya, Marouane; Eustache, Florence; Sifer, Christophe; Lévy, Vincent; Grynberg, Michaël; Sermondade, Nathalie
Abstract: Fertility preservation embraces different techniques developed to improve young women chances of becoming mothers after healing. Among them, in vitro maturation (IVM) procedure is based on oocyte retrieval without any gonadotropin treatment, feasible under locoregional or local anesthesia, with very low operative complications. The present retrospective analysis of a preliminary case series of 25 women diagnosed with Hodgkin or non‐Hodgkin lymphoma aims to evaluate the feasibility of IVM for urgent fertility preservation purposes in hematological context. A median of five mature oocytes was cryopreserved after one cycle of IVM, performed without delaying the start of the chemotherapy (median delay from histological diagnosis to start of the chemotherapy 17.5 days). No association was found between lymphomas' characteristics and the number of recovered or frozen oocytes. Although experimental, this technique could be relevant when fertility preservation has to be performed within a short time frame and without additional surgery nor any risk of malignant cells reintroduction.